Factors that influence the ways univrsity students think about referencing and related concepts - Mbutho, N.P.; Hutchings, C. (South African Journal of Higher Education, 2019)
ABSTRACT The role and importance of referencing is underestimated and neglected by university students globally. Literature illustrate that poor referencing practices might contribute to the persistent rise of plagiarism in higher educational institutions all over the world. Persistent poor referencing practices observed among our students at one of the South African universities led me to examine the socio-educational and cultural factors that influence the ways university students think about referencing and related concepts. This study interviewed fifteen third and fourth year students from one South African University of Technology. Grounded theory coding revealed that despite different cultural and schooling backgrounds, the majority of the students received their first formal referencing training at the university. The students felt that the training provided at our university was not in-depth, practical or extensive enough. Students reported that the reading and writing practices in high school were limited to memorising and regurgitating chunks of text from authoritative texts without necessarily being encouraged to acknowledge sources of information. The students were used to being given all the information considered necessary by teachers in class, and therefore saw no need to search for information themselves. It is therefore imperative that students are introduced to extensive referencing training and be trained to think critically about what they read from the first year of their study through to postgraduate studies.